Hydrogel-derived soft materials for biomimetic and energy-related functions - Goudappagouda; Wakchaure, V. C.; Ranjeesh, K. C.; Babu, S. S. (Australian Journal of Chemistry, 2016)
Supramolecular assembly of molecules leading to gelation of large amount of solvents is always a fascinating topic of research. In the very recent past, the exciting developments have marked hydrogels as intriguing materials with excellent features. Hydrogel scaffolds enable the accommodation of organic and/or inorganic guest materials to deliver diverse applications. Hydrogels have been exploited to generate soft materials with mechanical anisotropy, tunable rigidity, self-healing properties, as well as photocatalytic capabilities towards H2 production. Remarkably, the combination of a photocatalyst and a light-harvesting system in the gel matrix provides a unique means to photocatalytic H2 production. The biomimetic applications of hydrogels have also generated much attraction due to their potential demonstrations. The diverse applications underline the significance of such a soft gel medium to reach the final goal. Herein, important reports pertaining to the use of hydrogels as an effective way to generate advanced materials for biomimetic and energy-related issues are discussed.

Paintable room-temperature phosphorescent liquid formulations of alkylated bromonaphthalimide - Goudappagouda; Manthanath, A.; Wakchaure, V. C.; Ranjeesh, K. C.; Das, T.; Vanka, K.; Nakanishi, T.; Babu, S. S. (Angewandte Chemie - International Edition, 2019)
Organic phosphors have been widely explored with an understanding that crystalline molecular ordering is a requisite for enhanced intersystem crossing. In this context, we explored the room‐temperature phosphorescence features of a solvent‐free organic liquid phosphor in air. While alkyl chain substitution varied the physical states of the bromonaphthalimides, the phosphorescence remained unaltered for the solvent‐free liquid in air. As the first report, a solvent‐free liquid of a long swallow‐tailed bromonaphthalimide exhibits room‐temperature phosphorescence in air. Doping of the phosphor with carbonyl guests resulted in enhanced phosphorescence, and hence a large‐area paintable phosphorescent liquid composite with improved lifetime and quantum yield was developed.

Squaraine-linked metalloporphyrin two-dimensional polymer photocatalyst for hydrogen and oxygen evolution reactions - Ranjeesh, K. C.; George, L.; Wakchaure, V. C.; Goudappagouda; Devi, R. N.; Babu, S. S. (Chemical Communications, 2019)
Efficient water splitting photocatalysts are an energetically demanding and cost-effective method for generating renewable energy. Significant research has been reported to advance this approach. However, the use of organic photocatalysts and the presence of residual catalysts trapped in the porous frameworks present major concerns about the efficiency of this strategy. Herein, we report the photocatalytic evolution of H2 and O2 by a multi-hydroxyl group-decorated metalloporphyrin-based two-dimensional catalyst developed via metal catalyst-free synthetic route. Though metalloporphyrins have long been used for catalytic functions, a heterogeneous photocatalyst delivering both H2 and O2 has not yet been realized. This polymer catalyst design enables the photocatalytic diatomic O2 release, a bottleneck in water splitting, in a facile way. Photocatalytic release of H2 as well as O2 occurs with long-term durability of 20 cycles in 300 days with negligible decrease in efficiency, thus demonstrating the excellent performance of this new catalyst.